Clinical characteristics and epidemiology of sepsis in the neonatal intensive care unit in the era of multi-drug resistant organisms: A retrospective review - Dawood Yusef; Tala Shalakhti; Samah Awad; Hana'a Algharaibeh; Wasim Khasawneh (Elsevier, 2018)
Background: Sepsis in the neonatal intensive care unit (NICU) remains one of the most significant causes of morbidity and mortality, especially for preterm newborns. Multi-drug resistant organisms (MDROs) are emerging as important pathogens that cause neonatal sepsis in NICU. Therefore, studying the epidemiology, clinical features, and outcome caused by MDROs vs. non-MDROs, and identifying risk factors that may predispose patients to sepsis by MDROs are important. Methods: Episodes of blood culture-proven sepsis (age: 0-90 days) in the NICU at our institution from January 2012 to December 2015 were retrospectively reviewed. Collected data included demographics, signs at time of sepsis, laboratory values, microbiologic results, and final outcome. We compared clinical and laboratory data and final outcome for patients with sepsis due to MDROs vs. non-MDROs. Multivariate analysis was performed on variables with a P value of <0.05 from univariate analysis. Results: Sixty-eight episodes of sepsis (ages 0-54 days, median 7 days; 34 female; 81% premature) were caused by Gram-negative bacteria (n = 42; 62%), Gram-positive bacteria (n = 21; 31%), or Candida (n = 5; 7%). The most common organisms that were isolated were Acinetobacter baumannii (27%), Klebsiella pneumoniae (22%), coagulase-negative staphylococcus (CoNS) (18%), group B streptococcus (10%), and Escherichia coli (6%). Compared with non-MDROs (n = 16; 31%, excluding CoNS and Candida), MDROs (n = 35; 69%) were associated with higher mortality (P = 0.002) and more delay in providing targeted antimicrobial therapy (P = 0.002) (based on antimicrobial susceptibility tests). Sepsis due to the most resistant organisms (A. baumannii and K. pneumoniae Carbapenemase [KPC]-producing bacteria, n = 20; 39%) was associated with higher mortality (P = 0.001) and significantly associated with exposure to carbapenem and vancomycin before onset of sepsis (cases exposed = 13/20; 65%, P < 0.001). Conclusion: MDROs are the most common cause of sepsis at our NICU and are associated with higher mortality compared with non-MDROs. Previous exposure to carbapenem and vancomycin was associated with sepsis caused by the most resistant organisms.